2008
DOI: 10.1111/j.1442-2050.2007.00802.x
|View full text |Cite
|
Sign up to set email alerts
|

The utility of FDG-PET in the preoperative staging of esophageal cancer

Abstract: Accurate staging of esophageal cancer is important when determining which patients will potentially benefit from curative surgery. The aim of this study was to evaluate the incremental effect of 2-fluoro-2-deoxyglucose positron emission tomography (FDG-PET) when used in addition to standard staging modalities. Patients referred to two surgeons in an Australian metropolitan teaching hospital with esophageal or esophago-gastric junction malignancy between May 2002 and December 2006 were included. Patients who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
1
15
0
1
Order By: Relevance
“…PET/CT led to a change in the management plan of 17% of patients, with occult metastases being detected in 11%. This latter figure is similar to that reported by the three earlier smaller studies of PET/CT; it is considerably lower, however, than that reported by many earlier studies of PET where unexpected metastases, not demonstrated by CT or EUS, were detected in up to 25% of patients [2,3,11,12]. This is likely because all MDCT examinations were reviewed by a gastrointestinal specialist radiologist, with specific expertise in oesophageal MDCT, at a centralised multidisciplinary meeting before referral for PET/CT.…”
Section: Impact Of Pet/ct On Staging Of Diseasesupporting
confidence: 85%
See 3 more Smart Citations
“…PET/CT led to a change in the management plan of 17% of patients, with occult metastases being detected in 11%. This latter figure is similar to that reported by the three earlier smaller studies of PET/CT; it is considerably lower, however, than that reported by many earlier studies of PET where unexpected metastases, not demonstrated by CT or EUS, were detected in up to 25% of patients [2,3,11,12]. This is likely because all MDCT examinations were reviewed by a gastrointestinal specialist radiologist, with specific expertise in oesophageal MDCT, at a centralised multidisciplinary meeting before referral for PET/CT.…”
Section: Impact Of Pet/ct On Staging Of Diseasesupporting
confidence: 85%
“…The use of FDG PET to improve the accuracy of staging oesophageal cancer has been well described [2,3,[9][10][11][12]. The largest study to date, involving 199 patients, reported upstaging by PET of just 4% of patients, leading the authors to conclude that it offered limited additional value over a comprehensive staging protocol, consisting of CT, EUS and neck US with selective FNA cytology, and that its widespread introduction into routine clinical practice was questionable [4].…”
Section: Impact Of Pet/ct On Staging Of Diseasementioning
confidence: 95%
See 2 more Smart Citations
“…Accurate and comprehensive preoperative staging with computed tomography, positron emission tomography (PET) scanning, endoscopic ultrasound (EUS) and laparoscopy improves patient selection for surgery by excluding those with metastases and may increase postoperative survival. [8][9][10] Determinants of outcomes from oesophageal cancer surgery include hospital volume (as a proxy measure for surgeon and/or facility experience), hospital peer group classification, tumour stage and location and patient comorbidity. [11][12][13][14][15] Outcomes which are frequently measured include in-hospital mortality, morbidity and survival.…”
Section: Introductionmentioning
confidence: 99%